Bahan Ajar Berbasis Task Analysis untuk Guru dalam Pembelajaran Self-Care pada Siswa MDVI - Nasri, Yosa Yulia; Yuliana, Syari; Taufan, Johandri (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to identify self-care skills in MDVI students, produce suitable teaching materials for teachers using a task analysis strategy that includes identifying content, classifying the stages to be achieved, and breaking tasks down into detailed and systematic components. The method used is the ADDIE development model. The research was conducted in special schools across West Sumatra among MDVI students and their respective teachers. The study involves material experts and media experts. The research results show that the teachers' need for learning materials developed in self-care learning based on task analysis, the feasibility of the learning materials based on content validation is 4.60% (very good) and for media experts 4.92% (very good). The learning material product is effectively used based on the comparison of the pre-test and post-test results of teachers with an average increase of 30%, while for students, the average increase is 31.25%.